Association between health insurance status and malignant glioma. Issue 5 (6th June 2020) - Fischer, Igor; Mijderwijk, Hendrik-Jan; Kahlert, Ulf D; Rapp, Marion; Sabel, Michael; Hänggi, Daniel; Steiger, Hans-Jakob; Forster, Marie-Therese; Kamp, Marcel A
Abstract: Background: Prior studies have suggested an association between patient socioeconomic status and brain tumors. In the present study we attempt to indirectly validate the findings, using health insurance status as a proxy for socioeconomic status. Methods: There are 2 types of health insurance in Germany: statutory and private. Owing to regulations, low- and middle-income residents are typically statutory insured, whereas high-income residents have the option of choosing a private insurance. We compared the frequencies of privately insured patients suffering from malignant neoplasms of the brain with the corresponding frequencies among other neurosurgical patients at our hospital and among the German population. To correct for age, sex, and distance from the hospital, we included these variables as predictors in logistic and binomial regression. Results: A significant association (odds ratio [OR] = 1.59, CI = 1.45-1.74, P < .001) between health insurance status and brain tumors was found. The association is independent of patients' sex or age. Whereas privately insured patients generally tend to come from farther away, such a relationship was not observed for patients suffering from brain tumors. Comparing the out of house and in-house brain tumor patients showed no selection bias on our side. Conclusion: Previous studies have found that people with a higher income, level of education, or socioeconomic status are more likely to suffer from malignant brain tumors. Our findings are in line with these studies. Although the reason behind the association remains unclear, the probability that our results are due to some random effect in the data is extremely low.